Employee compensation, training and financial performance during the COVID-19 pandemic - Rabie Mahssouni; Mohamed Noureddine Touijer; Mohamed Makhroute (Journal of Risk and Financial Management, 2022)
The purpose of this paper is multi-faceted: first, to analyze the impact of employee compensation and training on firms' financial performance and the moderating effect of the COVID-19 pandemic on the relationship between employee compensation and financial performance, as well as the relationship between training and financial performance; and second, to analyze the decision-making process pertaining to these two aspects of human resources both prior to and during the COVID-19 pandemic. This study utilizes a sample of 103 Belgian pharmaceutical firms whose financial statements were published in the Bureau Van Djik database between 2012 and 2021. The estimation approach employed was panel data analysis, and the Generalized Method of Moments was used to evaluate the robustness of the system. Whether or not a crisis exists greatly alters the parameters that influence a pharmaceutical company's business performance. Specifically, the results reveal that the COVID-19 pandemic had a substantial and negative impact on financial performance. Human resource factors, which include employee compensation and training, more accurately explain the company's performance. The key contribution of such an approach is to illustrate that human resource-related factors have an impact on performance indicators during various types of crises, thereby assisting HR managers in making the best decision during times of crisis. It provides basic guidelines for policymakers to adhere to in order to have a better knowledge of how human capital characteristics might be utilized to improve the performance of their businesses during times of crisis. In addition, this research demonstrates that the firm's unique characteristics may affect the success of Belgian businesses.
Keywords: 650; performance; pharmaceutical industry; panel data; Belgium; human resources